Waiting for shelter: Perspectives on a homeless shelter's procedures - Brown, Molly; Mihelicova, Martina; Lyons, Jennifer; DeFonzo, Jennifer; Torello, Samantha; Carrion, Andres; Ponce, Allison N. (Journal of Community Psychology, 2017)
Research on homeless shelter implementation is limited. Some shelters have lengthy waitlists, which raises important questions about implications of waitlists for individuals with immediate shelter needs. This study used qualitative methods to understand the experiences of shelter seekers who were on a shelter waitlist (N = 59), including individuals who entered the shelter from the waitlist, and those removed from the shelter waitlist for procedural reasons. The average waitlist time was nearly 3 weeks, and 22.0% stayed at least one night on the street or another public place while on the waitlist. Responses to open-ended questions regarding barriers and effectiveness of the shelter referral procedures revealed 4 themes: procedural challenges, procedural benefits, benefits of the temporary stay, and communication challenges. Further research is needed to inform shelter implementation on a larger scale in accordance with current community-wide efforts to coordinate shelter services.
Keywords: dept.swk; female; human; major clinical study; male; night; patient referral; qualitative analysis